Preparation method of graft modified aramid pulp mother glue
Patent Information
- Application Number
- CN202611360779.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-03
- Publication Date
- 2026-10-20
AI Technical Summary
[0003]然而,其固有的物化特性导致在直接应用时面临两大根本性瓶颈:一是表面化学惰性导致的与聚合物基体界面结合弱;二是高比表面能及纤维间缠结导致的在基体中难以均匀分散
本发明将表面碱活化、TDI桥接、特定功能分子(如含巯基化合物)接枝与胶乳共混絮凝工艺进行创新性集成,旨在同时实现强界面化学键合、优异橡胶相容性/反应性及纳米级预分散的改性芳纶浆粕母胶的制备,在芳纶浆粕的表面通过两步接枝法引入能够与不饱和烯烃橡胶发生加成反应的巯基,能在后续与橡胶硫化过程中与橡胶形成化学键合,从而有效增强芳纶与橡胶间的界面作用力。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer materials, specifically relating to a method for preparing graft-modified aramid pulp masterbatch. Background Technology
[0002] Aramid pulp is a high-performance synthetic short fiber material derived from para-aramid (poly(p-phenylene terephthalamide), PPTA) fibers through a special fibrillation process. Its unique microstructure is characterized by a large specific surface area, abundant ciliary structure, and high aspect ratio. Compared to traditional aramid chopped fibers, aramid pulp not only inherits the inherent high strength, high modulus, excellent heat resistance, flame retardancy, and chemical stability of aramid fibers, but also, due to its fibrillated surface, can form more intricate physical entanglements and a larger contact area with the polymer matrix. This provides a theoretically significant advantage in improving the mechanical properties, wear resistance, dimensional stability, and fatigue life of composite materials. Therefore, aramid pulp is widely researched and applied in high-performance rubber products (such as seals, timing belts, and tire components), friction materials, reinforced plastics, and specialty paper-based materials, aiming to endow end products with superior overall performance.
[0003] However, its inherent physicochemical properties lead to two fundamental bottlenecks in direct application: first, its surface chemical inertness results in weak interfacial bonding with the polymer matrix; second, its high specific surface energy and interfiber entanglement make it difficult to disperse uniformly in the matrix. These two problems severely restrict the full realization of its reinforcing potential and directly affect the uniformity and reliability of the composite material's properties.
[0004] Currently, the industry's modification and application of aramid pulp mainly revolves around three technical paths: physical blending, surface modification, and masterbatch pre-dispersion. However, all have limitations to varying degrees: First, the simple physical-mechanical blending method is the most direct, but relying solely on shear force is insufficient to open the microscopic flocculent structure of the pulp, resulting in poor dispersion and no improvement in interfacial bonding, easily leading to uneven or even deteriorated composite material performance. Second, surface chemical modification is the main direction for improving interfacial affinity, including acid-base treatment, coupling agent coating, plasma treatment, and surface grafting polymerization. Among these, the method of selectively hydrolyzing the amide bonds on the surface of aramid pulp with a strong alkaline solution to introduce active amino groups (-NH2) into the surface provides an ideal anchoring point for subsequent chemical grafting reactions and is an effective surface activation method. However, simple surface activation treatment, without combining with effective subsequent coupling and dispersion processes, has limited improvement effects.
[0005] Among numerous chemical grafting strategies, utilizing diisocyanates (such as toluene diisocyanate, TDI) as "bridging molecules" is a classic and efficient approach. One end of the TDI isocyanate group (-NCO) undergoes a highly reactive addition reaction with amino groups generated from the hydrolysis of pulp, forming a strong chemical bond and anchoring the TDI molecule to the pulp surface. The other end retains an unreacted -NCO group. This group can further react with compounds containing active hydrogen (such as polyols and amines), introducing functional molecular segments into the pulp surface. This pathway exhibits good orientation and strong binding force, making it an effective method for constructing strong interfacial layers. However, in existing technologies, the subsequent utilization of the retained -NCO group is often limited to introducing conventional polymer segments (such as polyethers and polyester polyols) or reacting directly with components in the rubber compound. Research on the correlation between its design and the final composite material's processing characteristics and dynamic properties is insufficient, especially for rubber systems. The synergistic design of simultaneously improving interfacial bonding and processing dispersion through the introduced segments remains inadequate. For example, introducing active groups (such as thiol groups) that can participate in vulcanization is key to improving the performance of rubber masterbatches, and this is precisely an optimization direction of current technology.
[0006] Furthermore, masterbatch / predispersant technology is an effective way to solve dispersion problems and achieve industrial applications. This technology aims to pre-form a homogeneous concentrate with high-content fillers and a portion of the polymer carrier. Traditional aramid pulp masterbatch is mostly prepared using dry blending (such as internal mixing) or simple impregnation processes, which have limited dispersion scale and make it difficult to achieve sufficient dissociation and coating of nano / micron-level cilia. In contrast, latex blending flocculation provides a revolutionary approach to the preparation of high-performance masterbatch. This method uniformly mixes the modified pulp dispersion with polymer latex (such as natural latex, nitrile latex, etc.) in the liquid phase. Utilizing the extremely fine characteristics of latex particles, the polymer achieves in-situ, microscopic coating of pulp fibers during flocculation, thereby achieving fine dispersion of pulp and close contact with the polymer at the source. This method has a much better dispersion effect than the dry method, but the key prerequisite for success is that the surface of the pulp must be chemically modified so that it can be stably dispersed in the aqueous system and has good compatibility or reactivity with the latex particles. Otherwise, phase separation or reaggregation may still occur during the blending or flocculation process.
[0007] In summary, while existing technologies offer various solutions to the application challenges of aramid pulp, none have formed a coherent and synergistic solution from "intrinsic surface modification" to "macroscopically efficient dispersion." Simple chemical modification needs to be combined with dispersion processes; otherwise, the effects will be difficult to reflect in the final product. Conversely, dispersion processes (such as latex blending) cannot fully leverage their advantages without targeted surface chemical design. Therefore, developing such technologies has significant industrial value for fundamentally overcoming the application bottlenecks of aramid pulp in high-performance rubber composites and upgrading product quality. Summary of the Invention
[0008] To address the numerous problems and gaps in existing technologies, this invention provides a method for preparing graft-modified aramid pulp masterbatch. The method primarily utilizes toluene diisocyanate (TDI) and pentaerythritol tetra(3-mercaptopropionate) (PETMP) to sequentially graft aramid pulp activated by alkaline hydrolysis, introducing thiol groups capable of addition reactions with unsaturated olefin rubbers. These thiol groups can form chemical bonds with the rubber during subsequent vulcanization, effectively enhancing the interfacial forces between aramid and rubber. After blending with latex, demulsification and flocculation are performed, followed by drying to obtain the modified aramid pulp masterbatch. The obtained modified aramid pulp masterbatch is suitable for rubbers containing unsaturated double bonds. The strong interfacial forces between the aramid pulp and rubber effectively improve the tensile strength, tear strength, and fatigue resistance of the rubber.
[0009] The specific technical solution of the present invention is as follows: A method for preparing grafted modified aramid pulp masterbatch, the specific steps of which are as follows: (1) Soak the aramid pulp in 20-30 times its weight of acetone and clean it in an ultrasonic water bath to remove impurities such as spinning oil or sizing agent present on its surface. Then filter the aramid pulp and dry it at 60°C to remove acetone. (2) The above aramid pulp is immersed in a 1.8-2.2 mol / L potassium hydroxide or sodium hydroxide ethanol / water mixed solution at a weight ratio of 1:18-25, and the solution is heated to 75-82℃ and maintained for at least 1 hour to promote the hydrolysis reaction and achieve activation. Then the pulp is filtered and washed with water and anhydrous ethanol in sequence, and the activated aramid pulp is dried at 60℃. After the above treatment, the amide groups in the aramid fiber are hydrolyzed to produce amino and carboxyl groups, which provide active sites for further grafting reactions. The weight ratio of ethanol to water in the ethanol / water mixed solution is 3:1; the concentration of potassium hydroxide or sodium hydroxide is preferably 2 mol / L.
[0010] (3) Place the dried aramid pulp in a dry container, add acetone at a mass ratio of 1:20-30 (dried aramid pulp: acetone), and toluene diisocyanate (TDI) accounting for 15-30% of the mass of the dried aramid pulp. Heat to reflux and stir continuously for 1.5-2.5 hours. Then filter the aramid pulp and wash it several times with acetone. Preferably, the toluene diisocyanate accounts for 30% of the mass of the dried aramid pulp; This step is the first grafting reaction. The amino groups generated by hydrolysis on the surface of aramid undergo an addition reaction with the para-isocyanate groups in TDI, so that toluene diisocyanate is grafted onto the surface of the aramid pulp. (4) Place the aramid pulp treated in step (3) in a dry container, add 20-30 times the weight of the pulp in acetone and 10-20% of the weight of the pulp in pentaerythritol tetra(3-mercaptopropionate) (PETMP), heat to reflux and stir continuously, maintain the reaction for 0.5-1.5 hours, then filter the aramid pulp and wash it several times with ethanol to remove acetone; Preferably, pentaerythritol tetra(3-mercaptopropionate) accounts for 20% of the mass of the pulp; This step is the second grafting, which allows the isocyanate groups on the surface of the aramid pulp to react with the thiol groups in PETMP, thereby grafting thiol groups onto the surface of the aramid pulp. (5) Disperse the aramid pulp treated in step (4) in a mixed solution of ethanol:water in a volume ratio of 1:1, and mix it with latex with a total solid content of 3-4 times the mass of the aramid pulp and stir evenly. Then, slowly add calcium chloride aqueous solution while stirring continuously to demulsify and flocculate it. The solid obtained after flocculation is squeezed out of excess water by an open mill and then dried at 60°C to obtain the modified aramid pulp masterbatch.
[0011] Preferably, the latex is selected from natural rubber latex or nitrile rubber latex; the calcium chloride aqueous solution has a mass concentration of 8-15%, and its amount is 3-4 times the mass of the aramid pulp.
[0012] The above steps disperse aramid pulp by co-flocculation with latex, which is beneficial for the dispersion of aramid pulp in the compound rubber.
[0013] The aramid pulp masterbatch prepared by this method contains 20-25% aramid pulp. Thiol groups are grafted onto the surface of the aramid pulp through a two-step grafting method. During the subsequent vulcanization process of the aramid pulp reinforced compound, the thiol groups can undergo click chemical reactions with rubber molecules containing double bond groups, thereby connecting the aramid pulp and the rubber phase through chemical bonds and significantly enhancing the interfacial forces between the aramid pulp and the rubber phase.
[0014] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: This invention innovatively integrates surface alkali activation, TDI bridging, grafting of specific functional molecules (such as mercapto-containing compounds) with latex blending and flocculation processes. It aims to simultaneously achieve the preparation of modified aramid pulp masterbatch with strong interfacial chemical bonding, excellent rubber compatibility / reactivity, and nanoscale pre-dispersion. By introducing mercapto groups that can undergo addition reactions with unsaturated olefin rubber on the surface of aramid pulp through a two-step grafting method, mercapto groups can form chemical bonds with rubber during subsequent vulcanization, thereby effectively enhancing the interfacial forces between aramid and rubber. Attached Figure Description
[0015] Figure 1 The following are fine X-ray photoelectron spectra of sulfur in the aramid pulp samples treated in Example 1 and Comparative Examples 1-3. The comparison revealed that the characteristic peak of sulfur could be detected in the aramid pulp of Example 1 after two grafting steps, indicating that thiol groups were successfully grafted onto the surface of the aramid pulp treated according to Example 1. Figure 2 The stress-strain curves of the reinforced nitrile rubber in the blank control group, Example 1, and Comparative Examples 1-3 are shown. The comparison revealed that the stress-strain curve of the sample in Example 1 showed a significant increase in strength at different strains compared to the blank sample (without aramid pulp). The stress-strain curves of the comparative samples 1-3 exceeded those of the blank sample when the strain was less than 100%, but when the strain exceeded 100%, the strength of the three comparative samples was lower than that of the blank sample. The reason for this difference is that the comparative samples could not form chemical bonds with the rubber phase. As the strain gradually increased, the aramid pulp gradually debonded from the rubber phase, resulting in a rapid decrease in strength as the strain increased. In contrast, the sample in Example 1 was able to form chemical bonds with the rubber phase, so the aramid pulp did not easily debond from the rubber phase as the strain increased, and therefore its strength was always greater than that of the blank group. Figure 3 The results show the tensile fatigue life of the blank control group, Example 1, and Comparative Examples 1-3 reinforced nitrile rubber samples under different strains. The comparison shows that at 100% strain, the tensile fatigue life of both the example and the comparative sample is shorter than that of the blank sample. When the strain is 75%, the tensile fatigue life of each sample is relatively close. When the strain is 50%, the comparison shows that the tensile fatigue life of Example 1 is significantly higher than that of other samples, further proving that the two-step grafting method effectively enhances the interfacial force between aramid and rubber. Detailed Implementation
[0016] The technical solution of the present invention will be further described below with reference to specific embodiments. These embodiments are only used to illustrate the technical solution of the present invention in more detail and should not be construed as limiting the scope of protection of the present invention. The aramid pulp used in the following embodiments was purchased from Yantai Taihexing Materials Technology Co., Ltd. (Taparan 1820).
[0017] Example 1: A method for preparing graft-modified aramid pulp masterbatch, the specific steps of which are as follows: (1) Place the aramid pulp in a container, add 20 times the mass of the aramid pulp in acetone, and place it in an ultrasonic water bath for 30 minutes to remove impurities such as spinning oil or sizing agent present on its surface. Then, separate the aramid pulp by suction filtration and dry it at 60°C. (2) The above aramid pulp was immersed in a 2 mol / L potassium hydroxide ethanol-water mixed solution at a weight ratio of 1:20 (ethanol:water mass ratio of 3:1), heated to 80°C and maintained for 1 hour with constant stirring. After cooling, the aramid pulp was filtered out, washed 3 times with distilled water and then washed once with anhydrous ethanol. The aramid pulp was then dried at 60°C. (3) Place the dried aramid pulp in a heatable reflux container, add 25 times the mass of the dried aramid pulp in acetone, and add toluene diisocyanate accounting for 20% of the mass of the dried aramid pulp. Heat to reflux and maintain for 2 hours, stirring continuously during the process. After cooling, filter out the aramid pulp and wash it three times with acetone. (4) Transfer the aramid pulp after the above treatment into a heatable reflux container, add 25 times its mass of acetone and 15% of its mass of pentaerythritol tetra(3-mercaptopropionate), heat to reflux and keep stirring for 1.5 hours, and after cooling, filter out the aramid pulp and wash it three times with anhydrous ethanol. (5) Disperse the above-treated aramid pulp in a 50-fold mass of ethanol:water mixture with a mass ratio of 1:1, then add nitrile latex with a solid content of 4 times the mass of the above aramid pulp and mix evenly. Add 10wt% calcium chloride aqueous solution with a mass of 4 times the mass of the above aramid pulp under stirring to demulsify and flocculate it. Then, remove excess water by passing the obtained solid through a two-roll mill and dry it at 60°C to obtain modified aramid pulp masterbatch with nitrile rubber matrix.
[0018] Example 2: A method for preparing grafted modified aramid pulp masterbatch, the specific steps of which are as follows: (1) Place the aramid pulp in a container, add 20 times the mass of the aramid pulp in acetone, and place it in an ultrasonic water bath for 30 minutes. Then separate the aramid pulp by suction filtration and dry it at 60°C. (2) The above aramid pulp was immersed in a 2 mol / L potassium hydroxide ethanol-water mixed solution at a weight ratio of 1:25 (ethanol:water mass ratio of 3:1), heated to 80°C and maintained for 1 hour with constant stirring. After cooling, the aramid pulp was filtered out, washed 3 times with distilled water and then washed once with anhydrous ethanol. The aramid pulp was then dried at 60°C. (3) Place the dried aramid pulp in a heatable reflux container, add 25 times the mass of the dried aramid pulp in acetone, and add toluene diisocyanate accounting for 20% of the mass of the dried aramid pulp. Heat to reflux and maintain for 2 hours, stirring continuously during the process. After cooling, filter out the aramid pulp and wash it three times with acetone. (4) Transfer the aramid pulp after the above treatment into a heatable reflux container, add 25 times its mass of acetone and 15% of its mass of pentaerythritol tetra(3-mercaptopropionate), heat to reflux and keep stirring for 1.5 hours, and after cooling, filter out the aramid pulp and wash it three times with anhydrous ethanol. (5) Disperse the above-treated aramid pulp in a 50-fold mass of ethanol:water mixture with a mass ratio of 1:1, then add natural latex with a solid content of 4 times the mass of the above aramid pulp and mix evenly. Add 10wt% calcium chloride aqueous solution with a mass of 4 times the mass of the above aramid pulp under stirring to demulsify and flocculate it. Then, remove excess water by passing the obtained solid through a two-roll mill and dry it at 60°C to obtain modified aramid pulp masterbatch with nitrile rubber matrix.
[0019] The above examples illustrate that this method can be used to prepare aramid pulp masterbatch modified with natural rubber and nitrile rubber bases. These two types of rubber contain unsaturated double bond structures and are often used in the industry to blend with other non-polar and polar rubbers. Therefore, it can be used to prepare masterbatches suitable for other rubber types in a wide range of applications.
[0020] Comparative Example 1: This comparative example is a nitrile rubber matrix masterbatch prepared from untreated aramid pulp. The specific preparation steps are as follows: (1) Place the aramid pulp in a container, add 20 times the mass of the aramid pulp in acetone, and place it in an ultrasonic water bath for 30 minutes. Then separate the aramid pulp by suction filtration and dry it at 60°C. (2) The above aramid pulp is dispersed in a 1:1 mixture of ethanol and water with a solid content of 50 times the mass of aramid pulp, and mixed evenly with nitrile latex with a solid content of 4 times the mass of pulp. Under stirring, 10wt% calcium chloride aqueous solution with a solid content of 4 times the mass of aramid pulp is added to demulsify and flocculate the latex. The resulting solid is then passed through a rolling mill to remove excess water, and then dried at 60°C to obtain modified aramid pulp masterbatch with nitrile rubber matrix.
[0021] Comparative Example 2: This comparative example is a nitrile rubber matrix masterbatch prepared from aramid pulp that has only undergone alkali activation treatment. The specific preparation steps are as follows: (1) Place the aramid pulp in a container, add 20 times the mass of the aramid pulp in acetone, and place it in an ultrasonic water bath for 30 minutes to remove impurities such as spinning oil or sizing agent present on its surface. Then, separate the aramid pulp by suction filtration and dry it at 60°C. (2) The above aramid pulp was immersed in a 2 mol / L potassium hydroxide ethanol-water mixed solution at a weight ratio of 1:20 (ethanol:water mass ratio of 3:1), heated to 80°C and maintained for 1 hour with constant stirring. After cooling, the aramid pulp was filtered out, washed 3 times with distilled water and then washed once with anhydrous ethanol. The aramid pulp was then dried at 60°C. (3) Disperse the above aramid pulp in a 1:1 mixture of ethanol and water at a ratio of 50 times the mass of aramid pulp, and mix it evenly with nitrile latex at a solid content of 4 times the mass of pulp. Add 10wt% calcium chloride aqueous solution at a mass of 4 times the mass of aramid pulp under stirring to demulsify and flocculate it. Then, remove excess water by passing the obtained solid through a rolling mill and dry it at 60°C to obtain modified aramid pulp masterbatch with nitrile rubber matrix.
[0022] Comparative Example 3: This comparative example is a nitrile rubber matrix masterbatch prepared from aramid pulp that has undergone only one grafting treatment. The specific preparation steps are as follows: (1) Place the aramid pulp in a container, add 20 times the mass of the aramid pulp in acetone, and place it in an ultrasonic water bath for 30 minutes to remove impurities such as spinning oil or sizing agent present on its surface. Then, separate the aramid pulp by suction filtration and dry it at 60°C. (2) The above aramid pulp was immersed in a 2 mol / L potassium hydroxide ethanol-water mixed solution at a weight ratio of 1:20 (ethanol:water mass ratio of 3:1), heated to 80°C and maintained for 1 hour with constant stirring. After cooling, the aramid pulp was filtered out, washed 3 times with distilled water and then washed once with anhydrous ethanol. The aramid pulp was then dried at 60°C. (3) Place the dried aramid pulp in a heatable reflux container, add 25 times the mass of the dried aramid pulp in acetone, and add 30% of the mass of the dried aramid pulp in toluene diisocyanate. Heat to reflux and maintain for 2 hours, stirring continuously. After cooling, filter out the aramid pulp and wash it three times with acetone. Then dry it at 60°C. (4) Disperse the above aramid pulp in a 1:1 mixture of ethanol and water at a ratio of 50 times the mass of aramid pulp, and mix it evenly with nitrile latex at a solid content of 4 times the mass of pulp. Add 10wt% calcium chloride aqueous solution at a mass of 4 times the mass of aramid pulp under stirring to demulsify and flocculate it. Then, remove excess water by passing the obtained solid through a rolling mill and dry it at 60°C to obtain modified aramid pulp masterbatch with nitrile rubber matrix.
[0023] Figure 1 The X-ray photoelectron fine energy spectrum of sulfur in the aramid pulp samples treated in Example 1 and Comparative Examples 1-3 is shown. By comparison, it can be found that the characteristic peak of sulfur can be detected in the aramid pulp of Example 1 after two grafting steps, indicating that thiol groups were successfully grafted onto the surface of the aramid pulp treated in Example 1.
[0024] Experimental Example The aramid pulp masterbatch prepared in Example 1 and Comparative Examples 1-3 were mixed with 100 parts by weight of nitrile rubber, 55 parts by weight of carbon black (N330), 5 parts by weight of plasticizer (DOS), 6 parts by weight of activator, and 4.7 parts by weight of vulcanizing agent in an internal mixer to prepare compound rubber. The batching, mixing, and subsequent vulcanization processes were carried out in accordance with GB / T 6038-2006 (Rubber Test Compound Batching, Mixing and Vulcanization Equipment and Operating Procedures). The blank group consisted of 104 parts by weight of nitrile rubber, and the other preparation conditions were the same as those of the other experimental groups.
[0025] The vulcanization characteristics of each sample were tested according to GB / T 9869.3-2025 (Determination of vulcanization characteristics of rubber using a vulcanizing apparatus - Part 3: Rotorless vulcanizing apparatus). After compression molding, the compounded rubber was prepared into standard specimens. The specimens were subjected to stress-strain performance testing according to GB / T 528-2009 (Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber), right-angle tear strength testing according to GB / T 529-2008 (Determination of tear strength of vulcanized rubber or thermoplastic rubber (trouser-type, right-angled crescent-shaped specimens)), and tensile fatigue life testing according to GB / T 1688-2008 (Determination of tensile fatigue of vulcanized rubber). The test results are shown in Tables 1 and 2 below. Figure 2 and 3 As shown.
[0026] After comparing the embodiments and comparative examples, the corresponding performance is shown in the table below: Table 1 Comparison of vulcanization characteristics of various samples t in Table 1 10 and t 90 M represents scorch time and positive vulcanization time, respectively. L and M HThese represent the minimum and maximum torque of the rubber compound, respectively, and tanδ represents the loss factor. After comparison, it can be found that the modified aramid pulp does not have a significant impact on the vulcanization performance of the compound.
[0027] Table 2 Comparison of mechanical properties of each sample By comparison, it can be found that the hardness of the sample in Example 1 is basically the same as that of the comparative sample, while the 100%, 200%, and 300% tensile strength and tensile strength are significantly improved, and the tear strength is slightly improved compared with the comparative sample. This indicates that the modified grafting method enhances the interfacial force between the aramid pulp and the rubber phase.
[0028] Figure 2 The stress-strain curves of the reinforced nitrile rubber (NBR) samples (blank control group, Example 1, and Comparative Examples 1-3) were obtained. Comparison revealed that the stress-strain curve of the Example 1 sample showed significantly improved strength at different strains compared to the blank control group (without aramid pulp). While the stress-strain curves of the comparative examples exceeded those of the blank control group at strains below 100%, the strength of all three comparative examples was lower than that of the blank control group after strain exceeded 100%. This difference is attributed to the fact that the comparative examples could not form chemical bonds with the rubber phase. As strain gradually increased, the aramid pulp gradually debonded from the rubber phase, leading to a rapid decrease in strength. In contrast, the Example 1 sample could form chemical bonds with the rubber phase, preventing easy debonding of the aramid pulp during strain increases, thus maintaining a higher strength than the blank control group.
[0029] Figure 3 The tensile fatigue life test results of the blank control group, Example 1, and Comparative Examples 1-3 reinforced nitrile rubber under different strains are presented. The comparison shows that at 100% strain, the tensile fatigue life of the examples and comparative examples is shorter than that of the blank group. At 75% strain, the tensile fatigue lives of the samples are relatively similar. However, at 50% strain, the tensile fatigue life of Example 1 is significantly higher than that of the other samples, further demonstrating that the two-step grafting method effectively enhances the interfacial force between the aramid and rubber phases.
[0030] pass Figure 2 and 3 As shown in Table 2, the aramid pulp masterbatch sample after two-step grafting (Example 1) showed a 31% increase in 100% elongation strength, a 15% increase in tensile strength, and a significantly improved tensile fatigue life at 50% strain compared to the unmodified pulp masterbatch sample (Comparative Example 1).
[0031] In summary, this method can graft thiol groups onto the surface of aramid pulp and form chemical bonds with rubber during the subsequent vulcanization process with the compound, thereby improving the interfacial interaction between aramid pulp and rubber and enhancing the modulus, strength, and tensile fatigue performance under low strain of the modified aramid pulp-reinforced rubber.
[0032] The present invention has been described in detail with reference to the preferred embodiments described above, but the present invention is not limited thereto. Without departing from the spirit and essence of the present invention, those skilled in the art can make various equivalent modifications or substitutions to the embodiments of the present invention, and such modifications or substitutions should all be within the scope of the present invention. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should also be covered within the protection scope of the present invention.
Claims
1. A method for preparing graft-modified aramid pulp masterbatch, characterized in that, The specific steps are as follows: (1) The aramid pulp was soaked in acetone and cleaned in an ultrasonic water bath. Then the aramid pulp was filtered and dried at 60°C to remove the acetone. (2) The above aramid pulp is immersed in a 1.8-2.2 mol / L potassium hydroxide or sodium hydroxide ethanol / water mixed solution at a weight ratio of 1:18-25, and the solution is heated to 75-82℃ and maintained for at least 1 hour to promote the hydrolysis reaction and achieve activation. Then the pulp is filtered and washed with water and anhydrous ethanol in sequence, and the activated aramid pulp is dried at 60℃. (3) Place the dried aramid pulp in a dry container, add acetone at a mass ratio of 1:20-30 (dried aramid pulp: acetone), and toluene diisocyanate accounting for 15-30% of the mass of the dried aramid pulp. Heat to reflux and stir continuously for 1.5-2.5 hours. Then filter the aramid pulp and wash it several times with acetone. (4) Place the aramid pulp treated in step (3) in a dry container, add 20-30 times the weight of the pulp in acetone and 10-20% of the weight of the pulp in pentaerythritol tetra(3-mercaptopropionate), heat to reflux and stir continuously, maintain the reaction for 0.5-1.5 hours, then filter the aramid pulp and wash it several times with ethanol to remove acetone; (5) Disperse the aramid pulp treated in step (4) in a mixed solution of ethanol:water in a volume ratio of 1:1, and mix it with latex with a total solid content of 3-4 times the mass of the aramid pulp and stir evenly. During the stirring process, slowly add calcium chloride aqueous solution to break the emulsion and flocculate it. After flocculation, squeeze out the excess water with an open mill and then dry it at 60°C to obtain the modified aramid pulp masterbatch.
2. The method for preparing graft-modified aramid pulp masterbatch according to claim 1, characterized in that, In step (1), the aramid pulp is soaked in 20-30 times its weight of acetone.
3. The method for preparing graft-modified aramid pulp masterbatch according to claim 1, characterized in that, In step (2), the weight ratio of ethanol to water in the ethanol / water mixed solution is 3:1; the concentration of potassium hydroxide or sodium hydroxide is 2 mol / L.
4. The method for preparing graft-modified aramid pulp masterbatch according to claim 1, characterized in that, The toluene diisocyanate mentioned in step (3) accounts for 30% of the mass of the dried aramid pulp.
5. The method for preparing graft-modified aramid pulp masterbatch according to claim 1, characterized in that, In step (4), pentaerythritol tetra(3-mercaptopropionate) accounts for 20% of the mass of aramid pulp.